PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS PENGENDALIAN INTERNAL PERSEDIAAN PADA MAHADESA GNE, MATARAM - ardani, cening; Animah, Animah; Jumaidi, L. Takdir (Jurnal Riset Akuntansi, 2023)
This study aims to test whether the information system has a significanteffect on the effectiveness of internal inventory control at Mahadesa GNE, Mataram. Based on the theory found, this research supports Theory of Reasoned Action (TRA) which explains that people will consider the norms of their attitudes and realize that accounting information systems will generate benefits for their users. This research was conducted using quantitative datain 2023. The population in this study were BUMDES partner staff/officers whocollaborated with PT Mahadesa GNE and all Mahadesa employees, with the sample criteria being officers responsible for the system run by Mahadesa GNE. The collected data was processed using SPSS software version 2.6. The results of this study indicate that the accounting information system has a very significant effect on the effectiveness of inventory internal control in Mahadesa GNE.